Proximity differences between forwards and defenders during goal scoring in soccer - Smith, S.; Bedwell, J.; Eldridge, D.; Pulling, C.; Conway, K.; Lloyd, G. (Scientific Journal of Sport and Performance, 2025)
The role of a forward player in soccer is to score goals by destabilising defensive systems. The act of goal scoring in open play is fast paced with players requiring perceptual ability to navigate the environment. The purpose of this research study was to explore goal scorers` ability to perceive and adapt to the environmental threats to goal scoring at different competitive levels. All open play goals scored by forward players in the 2022/23 English Premier League, Championship, League 1, and League 2 divisions were analysed. Four observers recorded the proximity of defenders to the goal scorer at the moment of assist pass and moment of finish. Results showed significant differences existed between the proximity of defenders to the goal scorer between the assist pass and finish. When data was isolated to one touch finish goals within highly offensive zones, a reducing pattern of significant difference was found as league standard decreased. Findings offer an insight into the perceptual ability of forward players to destabilise defensive systems. Recommendations for practice design and talent identification are proposed.